Performance and Emission Characteristics of a Four Stroke Spark Ignition Engine with Recirculation of Hot and Cold Exhaust Gases - Ganguly, Aritra; Nath Murmu, Baidya; Chakrabarti, Somnath (International Journal of Engineering and Technology, 2018)
An experiment has been conducted on a four-stroke, four-cylinder spark ignition engine with and without recirculation of exhaust gas for different loads at a constant speed. Two cases were considered, the first in which 10% and later 20% of the exhaust gas was directly supplied to the intake manifold at a temperature of 820Â°C, while in the second case the same proportions of exhaust gas were cooled in a heat-exchanger to a temperature of 210Â°C before supply. Engine performance parameters like brake specific fuel consumption, brake thermal efficiency were evaluated under those conditions and compared with the same engine operating without recirculation. The corresponding emission characteristics of the engine were also measured using an exhaust gas analyzer which measured the amount of NOx, CO, CO2 and un-burnt HC. The performance and emissions characteristics of the engine obtained with hot and cold EGR were compared with reference to the same engine operating without EGR. The study revealed that the performance of the engine was better in terms of brake thermal efficiency and brake specific fuel consumption with cold EGR compared to hot EGR. However, the emissions of CO and HC were higher with cold EGR compared to that of hot EGR. Â Â Â